ТЕОРЕТИЧНІ ОСНОВИ МАРКЕТИНГУ МІСТА - Kobylyatskyi, O.P. (Економіка та право, 2012)
The paper studies the essence of city marketing. The approaches existent in the literature concerning the content of the given concept are analyzed. The role of branding in city marketing is defined.